Stress Fractures in Female Cadets in Bangladesh Naval Academy during Training - Uddin, Md Borhan; Rahman, Md Anisur (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Stress fractures occur due to repetitive cumulative micro trauma on the bone over a period of time. These are common overuse injuries in military cadets and sports personnel during training. Stress fracture in female cadets is a rising cause of concern for its high prevalence. It increases morbidity, long term absence from training and significant economic loss. Objective: To find out the prevalence, time of occurrence and sites involved among the fresh female cadets during their basic training. Materials and Methods: A descriptive cross-sectional study was conducted during January 2011 to April 2017 in female cadets undergoing basic training at Bangladesh Naval Academy, Chittagong. A detailed history and physical assessment was performed of those presenting with pain, swelling or limping. Radiographic imagings were done to evaluate the symptoms. All cases of stress fractures were finally diagnosed on the basis of findings and were appropriately managed and followed up every two weeks till the time of union. Results: Eighteen cases out of 82 had clinical and radiological signs of stress fractures with an overall prevalence of 21.95%. Average age was 19 years (range 18-20). Highest prevalence was around 12 weeks of training. Common sites were tibia (40.90%), pelvis (40.90%) and fibula (9.09%). There was one metatarsal and one femoral neck fracture. All the fractures were treated conservatively and were healed in an average period of 7 weeks. All cadets returned to their full activity in an average period of ten weeks. Conclusion: Prevalence among the female naval cadets is high and probably underrated in this setting. For prevention, modifiable causes and risks factors must be evaluated and identified. A protractive approach for early detection and immediate management is indispensible to reduce the morbidity and early return to full activity. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 48-52